Quality maturity model: assessing organizational quality culture in palm oil organization (Upstream) / Hasmah Che Mat - Che Mat, Hasmah (Faculty of Plantation and Agrotechnology, 2019)
The purpose of this research is to facilitate commitment by directors of palm oil organization with matters of quality culture. As at today, there is yet a method to assess maturity level of palm oil organization. This can be achieved through a new interpretation of the quality culture concept, the Quality Maturity Mode Palm Oil Supply Chain. The QMMPOSC enables palm oil directors to assess their location in a way of quality culture, leading them to the next step forward, which allows them to progress in time and allow them to compare themselves with others and learn from good practices. This research involved a presentation of systematic literature review (SLR) on assessment of quality management maturity practices in palm oil organization and also relates to the Design Science Research Methodology as a framework and used Grounded theory, Focus Group Interview methods to create the QMMPOSC. The QQMPOSC defines 30 elements of quality culture, which are grouped into eight categories: Management of the organisation, environmental sensing, learning organisation attributes, attitude to change, attitude to quality, leadership, investment in staff, and alignment. The evaluation of tool had been conducted at 2 companies Felda and Tabung Haji Plantation. Both palm oil organizations already at level 4 which is managed level from five level of QMMPOSC. This is preliminary result of the study. QMMPOSC can be used as roadmap of maturity in palm oil organization to generate profit.